Analysis of the lethal interaction between the prune and Killer of prune mutations of Drosophila. - Biggs, J.; Tripoulas, N.; Hersperger, E.; Dearolf, C.; Shearn, A. (Genes & Development, 1988)
The third-chromosome mutation Killer of prune (K-pn) causes no phenotype by itself, but causes lethality in individuals homozygous for the nonlethal X-chromosome mutation prune (pn). We have recovered 12 gamma-ray-induced revertants of Killer of prune. All of the revertants fail to complement a recessive cell lethal mutation in the abnormal wing discs (awd) gene. We present evidence that Killer of prune is a mutation in the awd gene. First, revertant awdKR14 leads to reduced accumulation of the awd gene product, but does not affect flanking genes. Second, when a copy of the awd gene is cloned from Killer of prune homozygous flies and injected into embryos, transformants express the lethal interaction with prune. In individuals of the genotype pn; awdK-pn/awd+ the awd mRNA is present at normal levels but the awd polypeptide fails to accumulate. The absence of the awd gene product in such individuals is the cause of death. Although the awd polypeptide is a subunit of a cytoplasmic protein, its sequence is similar to subunit V of yeast cytochrome oxidase.